(untitled) (Revista Contexto & Saúde, 2026)
Introduction: Among acute cardiovascular diseases, venous thromboembolism is one of the most common complications in patients with gynecological cancer, due to prothrombotic state and exposure to vasculotoxic therapies. Objective: To evaluate the thromboembolic risk and the profile of anticoagulant use for prevention or treatment of VTE in patients with gynecological cancer, followed up in a specialized hospital. Methods: A cross-sectional study was carried out at the Hospital da Mulher, located in Salvador, Bahia in 1 year, consisting of analysis of medical records to track the profile of use and application of the Khorana, PROTECHT and Onkotev scores. Results: The electronic medical records of a population of 2,865 women were evaluated, and 117 patients were selected, with a mean age of 57.20 years. Malignant neoplasm of the cervix (42.74%) was the most frequent. The ROC curve determined that Onkotev score presented a better performance predictive of thromboembolic risk (AUC = 0.742; p = 0.000; CI-95: 0.651-0.833) in this sample than the Khorana (AUC = 0.567; p = 0.208; CI-95: 0.463-0.671) and PROTECHT (AUC = 0.517, p = 0.730, CI-95: 0.413-0.624) scores. Conclusion: This study is one of the first in Bahia to investigate the profile of anticoagulant use in this group. Onkotev presented itself as the one with the best performance among the others, however, its predictive accuracy remains limited, since it would be able to predict approximately 75% of the VTE cases that occurred. Further studies are needed to evaluate this topic.